Risk Analysis Of Construction Planning Affecting Quality, Time, and OHS Control on Management Performance in Warehouse and Logistics Industry - Muhammad Fauzi; Darmawan Pontan; Muhammad Zaki; Tulus Widiarso (Dinasti Publisher, 2025)
The logistics industry in Indonesia is growing in line with the increase in online transactions. Warehouse facilities play a crucial role in the logistics industry as they are essential for ensuring smooth business operations. Warehouses used for logistics purposes generally employ steel construction. The development of steel-structured warehouses carries considerable risks that can affect project completion time, project quality, occupational health and safety (OHS), and management performance. Therefore, management must be able to identify and analyze all potential risks during warehouse construction to ensure the project is completed with planned quality, OHS control, and timing. This study aims to identify the relationships among risk factors during the planning and construction phases with quality control, time, and OHS, which can influence management performance. Additionally, it seeks to measure the impact of project control, particularly in terms of quality, time, and OHS, on management performance in warehouse and logistics industry development. The research employs a quantitative descriptive method. Data analysis was conducted using Structural Equation Modeling (SEM) with the Smart PLS application. The study found that risks have a direct positive impact on quality control, time, and OHS but an insignificant negative impact on management performance. Furthermore, the findings indicate that quality control, time, and OHS significantly and positively influence management performance.